Incorporating a Sorghum Habitat for Enhancing Lady Beetles (Coleoptera: Coccinellidae) in Cotton - P. G. Tillman; T. E. Cottrell (Psyche: A Journal of Entomology)
Lady beetles (Coleoptera: Coccinellidae) prey on insect pests in cotton. The objective of this 2 yr on-farm study was to document the impact of a grain sorghum trap crop on the density of Coccinellidae on nearby cotton. Scymnus spp., Coccinella septempunctata (L.), Hippodamia convergens Guérin-Méneville, Harmonia axyridis (Pallas), Coleomegilla maculata (De Geer), Cycloneda munda (Say), and Olla v-nigrum (Mulsant) were found in sorghum over both years. Lady beetle compositions in sorghum and cotton and in yellow pyramidal traps were similar. For both years, density of lady beetles generally was higher on cotton with sorghum than on control cotton. Our results indicate that sorghum was a source of lady beetles in cotton, and thus incorporation of a sorghum habitat in farmscapes with cotton has great potential to enhance biocontrol of insect pests in cotton.